The lazy man’s way to riches - Nixon, Richard Gilly (Wiley, 2005)
The first half of The Lazy Man’s Way to Riches outlines ways to break self-destructive habits--such as the inability to make decisions or negative self-talk--and develop new ones to counteract them. The second half reveals the secrets to such invaluable business skills as starting a business and developing effective marketing skills. As one of the finest self-help and personal growth books ever written, The Lazy Man’s Way to Riches, 30th Anniversary Edition will inspire and instruct readers on the best ways to live their lives to the fullest.